Assessment of hyperbaric oxygenation treatment response in parotid glands by T2 mapping following radiotherapy for head and neck tumours - Vidmar, Jernej (Radiology and oncology (Ljubljana), 2022)
Background: The study was designed to evaluate the influence of hyperbaric oxygenation therapy (HBOT) on the parotid gland in patients following radiotherapy for head and neck tumours. Patients and methods: HBOT response was monitored by 3T magnetic resonance imaging (MRI) using T 2 mapping and subsequent measurement of mean T 2 and T 2 variability as well as by salivary tests (salivary flow, buffer capacity, and pH). Eighteen patients previously treated with irradiation doses between 50 and 80 Gy as well as 18 healthy gender and age matched controls were enrolled. MRI was performed prior to HBOT (40.2 ± 20 months after radiotherapy) and after 20 daily HBOT at 2.5 ATA (absolute atmosphere). Each HBOT consisted of breathing 100% oxygen for 90 minutes. Results: Significant differences in mean T 2 prior to HBOT were observed between the ipsilateral irradiated (121 ± 20 ms), contralateral parotids (107 ± 21) and control group (96 ± 12 ms). A positive correlation in patients between T 2 variability and irradiation dose was detected in contralateral parotids before HBOT (R = 0.489, p = 0.0287). In addition, negative correlations were observed between mean T 2 in the ipsilateral as well as the contralateral gland and salivary flow before and after HBOT. Negative correlations between mean T 2, T 2 variability and pH of unstimulated saliva were also observed in the sides of parotid before and after HBOT. Conclusions: The study confirmed that T 2 mapping had a potential for monitoring the differences between irradiated and normal parotid glands. It could also be useful in the assessment of the glandular tissue response to HBOT.
Keywords: head and neck tumours; hiperbarično zdravljenje s kisikom; hyperbaric oxygenation therapy; magnetno-resonančno slikanje; MRI; rak glave in vratu; T2 mapiranje; T2 mapping